2023
DOI: 10.1002/adem.202301525
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microstructure, Texture Evolution, and the Mechanism of Grain Refinement of Commercially Pure Titanium During Cold Rolling: Experiment and Simulation

Yuxing Sun,
Xirong Yang,
Xiaoyan Liu
et al.

Abstract: A comprehensive understanding of the microstructures and texture evolutions during the rolling process is of great significance for the preparations of high‐quality commercially pure titanium (CP‐Ti) sheets. Therefore, in the present work, the effects of rolling reductions on the microstructures and textures of CP‐Ti are investigated by optical microscope, electron backscatter diffraction, and X‐ray diffraction. A crystal plasticity finite element model (CPFEM) is developed to accurately predict the rolling de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…To enhance its comprehensive mechanical performance, cold rolling method combined with heat treatment is applied to refine grain sizes of commercial pure titanium (CP-Ti) [14][15][16]. Sun et al [17] investigated the impacts of the rolling reductions on the textures and microstructures evolutions of CP-Ti sheets and developed an accurate crystal plasticity finite element model to predict its rolling deformation behaviors. The results showed that the twins, including the extension twins and compression twins, and the slip become more likely contribute to the plastic deformations during the total rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance its comprehensive mechanical performance, cold rolling method combined with heat treatment is applied to refine grain sizes of commercial pure titanium (CP-Ti) [14][15][16]. Sun et al [17] investigated the impacts of the rolling reductions on the textures and microstructures evolutions of CP-Ti sheets and developed an accurate crystal plasticity finite element model to predict its rolling deformation behaviors. The results showed that the twins, including the extension twins and compression twins, and the slip become more likely contribute to the plastic deformations during the total rolling process.…”
Section: Introductionmentioning
confidence: 99%